Endoscopic deployment of multiple (≥ 3) metal stents for unresectable malignant hilar biliary strictures - Koshitani, Tatsuya; Nakagawa, Shuji; Konaka, Yoshitomo; Nakano, Keimei; Fuki, Shuichi; Itoh, Yoshito (Endoscopy International Open, 2019)
Background and study aims Endoscopic deployment of multiple (≥ 3) self-expandable metal stents (SEMS) for high-grade unresectable malignant hilar biliary strictures (UMHBS) is technically challenging. Eleven consecutive patients with high-grade UMHBS (mean age: 76 years, male/female: 5/6, Bismuth-Corlette classification IIIa/IV: 7/4) underwent endoscopic deployment of multiple SEMS using a combination of side-by-side (SBS) and stent-in-stent (SIS) methods. Technical and clinical success rates were 11/11. More than three SEMS were successfully deployed, and obstructive jaundice was fully improved in all cases. Stent occlusion was recognized in four of 11 patients (mean: 134 days, range: 28 – 232). Reinterventions for both liver lobes were feasible by passing the guide wire inside the previously placed stents in three of four patients. Median stent patency was 150 days during a mean follow-up period of 184 days (range: 37 – 558). Three patients developed self-limiting cholangitis without definite stent occlusion as late (> 30 days) adverse events. Employing the combination of SBS and SIS methods may facilitate endoscopic deployment of multiple SEMS to treat high-grade UMHBS.